2008
DOI: 10.1254/jphs.fm0070272
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Topics of Bone Metabolism: A Novel Bisphosphonate for the Treatment of Periodontitis

Abstract: Abstract. It has been reported that the pharmacological characteristics of bisphosphonates vary depending on the side chain attached to the carbon atom of the P-C-P bond. TRK-530 is a novel synthetic bisphosphonate with an anti-oxidant methylthio-phenylthio side chain. This compound has been suggested to have both anti-inflammatory and anti-bone-resorbing effects. Such a compound could be effective for the treatment of diseases with excessive bone resorption accompanied by inflammation. We have been studying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 14 publications
(4 reference statements)
1
17
0
7
Order By: Relevance
“…Moreover, it can impede the conversion of dicalcium phosphate dehydrate (DCPD) to hydroxyapatite and reduce pellicle formation. Bisphosphonates, which are stable synthetic analogs of pyrophosphate with resistance to hydrolysis, have also been used as anti-calculus agents (Shinoda et al, 2008;Sikder et al, 2004). When used as advanced mineralization inhibitors, polyphosphates (e.g., hexametaphosphate) can reduce calculus formation (Sikder et al, 2004).…”
Section: Strategies For Prevention Of Calculus Formationmentioning
confidence: 99%
“…Moreover, it can impede the conversion of dicalcium phosphate dehydrate (DCPD) to hydroxyapatite and reduce pellicle formation. Bisphosphonates, which are stable synthetic analogs of pyrophosphate with resistance to hydrolysis, have also been used as anti-calculus agents (Shinoda et al, 2008;Sikder et al, 2004). When used as advanced mineralization inhibitors, polyphosphates (e.g., hexametaphosphate) can reduce calculus formation (Sikder et al, 2004).…”
Section: Strategies For Prevention Of Calculus Formationmentioning
confidence: 99%
“…Bisphosphonates (BPs) are pyrophosphate analogs that can suppress osteoclastic bone resorption[46] Bisphosphonates are known to bind to hydroxyapatite crystals and prevent their dissolution in addition to increasing osteoblast differentiation and inhibiting osteoclast activation. [4] Giannobile WV has summarized and categorized the bone-specific actions of bisphosphonates at the tissue level (decrease bone turnover due to inhibition of bone resorption, decrease the number of new bone multicellular units resulting in a net positive whole body bone balance) and at cellular level (decrease osteoclast recruitment, osteoclast adhesion, depth of resorption site and release of cytokines by macrophages along with an increase in osteoclast apoptosis and osteoblast differentiation and number).…”
Section: Host Modulatory Therapymentioning
confidence: 99%
“…TRK-530 is a recently developed novel synthetic bisphosphonate with an anti-oxidant methylthio-phenylthio side chain (5). The nitrogen-containing bisphosphonates used were alendronate (Sigma-Aldrich, St. Louis, MO, USA), risedronate (Procter and Gamble Pharmaceutics, Wood Corners Laboratories, Norwich, NY, USA) and zoledronate (Novartis Pharma AG, Switzerland).…”
Section: Reagents (Bisphosphonates)mentioning
confidence: 99%
“…1). It has been reported that the pharmacological characteristics of bisphosphonates vary depending on the nature of the side chains (5). Bisphosphonates are also classified into nitrogen-containing and non-nitrogen-containing bisphosphonates.…”
Section: Introductionmentioning
confidence: 99%